Iniencephaly: Early Prenatal Diagnosis and Postdelivery Findings - Ahmet Cantuğ Çalışkan; Hakan Aytan; Fazlı Demirtürk (Medical Network, 2009)
Iniencephaly is a rare malformation characterized by occipital bone defect,cervical dysraphism and retroflexion of fetal head.Because of its lethal prognosis termination of pregnancy is recommended when this condition is diagnosed before viability.Early prenatally diagnosed cases are rare because careful and early ultrasonograhic evaluation is necessary.In this case report we present an iniencephaly early diagnosed by sonography,in which therapeutic abortus was induced and examined after delivery.